Comparison of tropospheric scintillation models on earth-space paths in tropical region - Abdul Rahim, Nadirah; Islam, Md Rafiqul; Mandeep, J S; Dao, Hassan (Maxwell Scientific Organization, 2012, 2012)

(untitled)
This study presents the comparison of the cumulative distribution of tropospheric scintillation models in order to see which model suits the best with the measured one. About six different models were compared and studied with the measured one. The scintillation data were taken from January 2011 till December 2011 which totals up to a 12 month period. This paper also presents the percentage fractional errors and RMS errors for scintillation fades and also scintillation enhancements. The findings show that the ITU-R has the highest RMS error for scintillation fades with value of 104.1%, whereas OTUNG has the highest RMS error for scintillation enhancements with value of 112.2%. The study also shows that Karasawa is the best model for scintillation fades, while Van de Kamp is the best model for scintillation enhancements.